Moche portraits from ancient Peru - Donnan, Christopher B. (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture, 2004)
"This book presents the first wide-ranging, systematic study of the Moche portraits. Drawing on more than 900 examples from museums and private collections around the world - some 300 of which are illustrated here in full color - Christopher Donnan documents how the portrait tradition evolved, how the portraits were produced and distributed, who they portrayed, why they were made, and how they were used in Moche society. His analysis is supported by extensive archaeological evidence, which provides the context for portraits found in Moche tombs and midden deposits, as well as useful information for identifying the headdresses and ornaments worn by the individuals portrayed." "This is the largest collection of Moche portraits that has ever been published. As one of the most remarkable groups of portraits produced by any ancient people, it will be of interest to all connoisseurs and scholars of the world's great art traditions, as well as to students of the Moche and prehistoric Andean peoples."--BOOK JACKET.